2009
DOI: 10.1007/dcr.0b013e3181a74111
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stapled Transanal Rectal Resection on Anorectal Function in Patients with Obstructed Defecation Syndrome

Abstract: Stapled transanal rectal resection allowed for the correction of rectocele and intussusceptions. These corrections increased rectal sensitivity, diminished symptoms of obstructed defecation syndrome, and improved the quality of life of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…a small residual prolapse was identified in 6 (13.3%) patients. imaging demonstrated complete disappearance of rectal intussusception in all patients, and the mean postoperative constipation score decreased from 13 (range, [8][9][10][11][12][13][14][15] to 5 (range, [3][4][5][6][7].…”
mentioning
confidence: 99%
“…a small residual prolapse was identified in 6 (13.3%) patients. imaging demonstrated complete disappearance of rectal intussusception in all patients, and the mean postoperative constipation score decreased from 13 (range, [8][9][10][11][12][13][14][15] to 5 (range, [3][4][5][6][7].…”
mentioning
confidence: 99%
“…21 Several studies confirm the safety and efficacy of the STARR procedure for management of ODS. [22][23][24] Also, the data collected from this clinical study suggest that 91% of the patients had a satisfactory symptomatic relief from digitations with significantly improved ODS score with the STARR procedure, coupled with a few intraoperative and postoperative complications. The most common intraoperative adverse event was bleeding from the staple line, which occurred in 48.57% of patients, so the anastomotic ring should be meticulously checked and carefully secured with stitches whenever necessary.…”
Section: Discussionmentioning
confidence: 66%
“…Given the outcome in relation to the tumour regression grade, this leads us to question the significance of the change in relationship to tumour response or whether this relates to flow and pressure and to vessel elasticity given the preoperative treatment. Reply to Akingboye et al [1] of our paper assessing the inferior mesenteric vein (IMV) diameter as a surrogate marker to evaluate response to neoadjuvant chemoradiotherapy (CRT) for locally advanced rectal adenocarcinoma [2]. They raise an interesting point regarding correlation of IMV diameter of whole-mount specimens with and without tumours, to validate the hypothesis [1].…”
mentioning
confidence: 93%
“…Reboa et al [2] found that the clinical improvement after STARR was associated with increased rectal sensitivity. Benoecki et al showed unfavourable faecal incontinence scores after STARR in patients with small rectal diameter, low squeeze pressure and increased pelvic floor descent [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation